The Effect of Role-Playing Methods on Aud's Social Interaction Skills at Mekar Mekarti Kindergarten, Pasangkayu Regency - Istikomah Istikomah; Durrotunnisa Durrotunnisa; Sita Awalunisah; Andi Agusniatih (Journal of Educational Sciences, 2026)
This study aims to determine the effect of role-playing methods on the development of children's social behavior at Mekar Mekarti Kindergarten in Pasangkayu Regency. Social behavior is an important skill that needs to be developed from an early age, including caring, cooperation, and mutual assistance. This study used a quantitative approach with a one-group pretest-posttest design, involving 15 children as research subjects. Data collection techniques included observation, interviews, and documentation, while data analysis was performed statistically using a t-test through the SPSS program. The results showed a significant increase in children's social behavior after being given treatment in the form of role-playing methods. The pretest average score of 4.93 increased to 8.13 on the posttest. In addition, the Not Yet Developed (BB) category, which previously dominated, decreased dramatically to 0% after the treatment, while the Developing as Expected (BSH) and Developing Very Well (BSB) categories increased significantly. The t-test showed a Sig. (2-tailed) value of 0.000 < 0.05, which means H0 is rejected and H1 is accepted, so it can be concluded that the role-playing method has a significant effect on children's social behavior. Thus, the role-playing method can be used as an effective learning strategy in developing the social aspects of early childhood.